2017
DOI: 10.1038/s41598-017-12931-1
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids and Alzheimer’s disease: a Mendelian randomization analysis

Abstract: We conducted a two-sample Mendelian randomization study to test the hypothesis that raised plasma levels of the branched-chain amino acids isoleucine, leucine, and valine are associated with Alzheimer’s disease (AD). From a genome-wide association study of 16,596 individuals of European ancestry, we obtained summary statistics for four independent single nucleotide polymorphisms (SNPs) associated with isoleucine levels and one SNP associated with both leucine and valine levels at genome-wide significance. Summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 23 publications
5
50
1
Order By: Relevance
“…Using Mendelian randomization (MR) Larsson and Markus suggested that individuals with a genetic predisposition to raised plasma isoleucine were positively associated with AD [53]. More recently, the BCAAs have been shown to have a predictive value for the development of new-onset diabetes up to 12 years after the baseline examination, which incidentally has a 50% increased risk of developing AD [56,57]. Conversely, in other conditions such as liver disease [58], traumatic brain injury (TBI) [59,60] and sepsis [61], levels of blood BCAAs are low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Mendelian randomization (MR) Larsson and Markus suggested that individuals with a genetic predisposition to raised plasma isoleucine were positively associated with AD [53]. More recently, the BCAAs have been shown to have a predictive value for the development of new-onset diabetes up to 12 years after the baseline examination, which incidentally has a 50% increased risk of developing AD [56,57]. Conversely, in other conditions such as liver disease [58], traumatic brain injury (TBI) [59,60] and sepsis [61], levels of blood BCAAs are low.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in other conditions such as liver disease [58], traumatic brain injury (TBI) [59,60] and sepsis [61], levels of blood BCAAs are low. In TBI, where brain glutamate is low, the plasma concentrations of the BCAAs are also decreased, whereas the concentrations of the AAA's (phenylalanine, tryptophan and tyrosine) are increased [57]. In patients recovering from TBI, BCAA supplementation has demonstrated a therapeutic benefit with improved cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find age-related hippocampal changes in isoleucine, leucine, or valine, their oxidation by NAD + in the BCKDH complex produces NADH, to maintain redox balance and feed OXPHOS. Increased BCAA metabolites in human plasma such as isoleucine are positively correlated with AD [81]. BCAAs are elevated with age in serum of human AD and 3xTg-AD mice [82].…”
Section: Branched Chain Amino Acidsmentioning
confidence: 97%
“…In prior in vitro studies using rat cortical slices, BCKA accumulation has also been demonstrated to reduce neuronal glutamate uptake [47], which has been identified as a potential pathological feature of Alzheimer's disease (AD) [48]. In addition, a genetic predisposition to elevated isoleucine has been found to increase risk of AD, and leucine has previously been shown to promote tau accumulation via a mammalian target of rapamycin (mTOR)-dependent mechanism [49,50]. An altered BCAA metabolism could therefore represent a potential mechanistic link between MetS and AD [51].…”
Section: Discussionmentioning
confidence: 99%